(untitled) - Robertson, Jack C. (Boston, 2002)
The Second Edition of AUDITING continues to reflect the rapidly changing audit environment and is based on a transaction cycles approach to the auditing course. Pany and Whittington keep students at the forefront of auditing practices by incorporating cutting-edge coverage of internal control and operational auditing. Illustrative cases use actual business and accounting examples, and are industry based to demonstrate how outcomes vary across a variety of dynamic scenarios. In addition, International Auditing standards are discussed, where appropriate, in order to profile the growing importance of global markets.
Keywords: Auditing